Reassessment of biochemically determined Hunter syndrome carrier status by DNA testing. Issue 8 (August 1998) - Timms, K M; Edwards, F J; Belmont, J W; Yates, J R; Gibbs, R A
Abstract : Deficiency of iduronate-2-sulphatase (IDS) results in the X linked recessive lysosomal storage disorder Hunter syndrome. Determination of carrier status in families affected by this disorder has been performed using a variety of enzymatic tests. None of these tests has proved to be 100% effective at identifying carriers. The aim of this study was to perform carrier testing in a family affected by the disorder, where testing was complicated by the fact that no surviving affected subjects were available for study. Direct dye primer sequencing of PCR products was used to identify mixed bases in an obligate carrier. Two mixed bases were observed within exon VIII. The first base change (T-->A) at nucleotide position 1150 results in a missense mutation (H342Q), while the second base change (G-->T) at nucleotide position 1151 results in a nonsense mutation (G343X). Four additional female family members were screened for the same mutation. Using this approach it is possible to provide unambiguous information about a subject's carrier status and, unlike biochemical testing, this approach will be equally effective when applied to families with the mild form of this disorder.